2022
DOI: 10.7759/cureus.24043
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Epidemiological Profiles of COVID-19 Elderly Patients in Guwahati City, Assam, India: A Cross-Sectional Study

Abstract: BackgroundAs of November 14, 2021, coronavirus disease 2019 (COVID-19 has affected more than 3,44,00,000 individuals in India and resulted in more than 4,60,000 deaths in India. Symptoms of COVID-19 include cough, fever, dyspnea, diarrhea, fatigue, expectoration, myalgia, hemoptysis, abdominal pain, and anorexia. Associated comorbidities such as hypertension, diabetes, cardiovascular illness, and respiratory sicknesses influence the severity and prognosis of the COVID-19. Therefore, this study was conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…All the symptomatic patients had fevers. A study by Patgiri PR et al found coughing to be the most common symptom, followed by fever and breathing difficulty [ 10 ]. Another study by Salins N et al shows that 81% of the elderly had mild symptoms of COVID [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the symptomatic patients had fevers. A study by Patgiri PR et al found coughing to be the most common symptom, followed by fever and breathing difficulty [ 10 ]. Another study by Salins N et al shows that 81% of the elderly had mild symptoms of COVID [ 11 ].…”
Section: Discussionmentioning
confidence: 99%